The relationship between the role of nurses and the satisfaction of patients and families of pulmonary tuberculosis sufferers in the treatment room of Jayapura city hospital - Frengky Apay; Rohmani Rohmani; Ardhanari Hendra Kusuma (Science Midwifery, 2022)
This study aims to determine the relationship between the role of nurses and patient and family satisfaction in nursing services at Jayapura City Hospital from the Feasibility Aspect (feasibility). Research Methods: This type of study is analytical observational with a cross-sectional design with a sample of 100 people consisting of 50 patients and 50 patient families. The sample collection method is accidental sampling. The selected statistical test analysis technique is the chi square test. Results: The results showed that the age of the most respondents was between 31-45 years (46%), the most types of gender were men 56%, the most education was high school, namely 37%, the level of satisfaction of patients and families with satisfied health facilities amounted to 67%, satisfaction with health services and nursing in the pulmonary room was satisfied (56%). The results of the cross-tabulation of bivariate analysis showed that there was a relationship between the role of the nurse and the satisfaction of patients and families which was assessed from the dimension of reliability with p-value (0.000), dimension of responsiveness (0.001 ), dimension of empathy (0.001), dimension of assurance (0.000), and dimension of physical evidence (0.000). Conclusion: there is a relationship between the role of nurses and the satisfaction of patients and families of patients with pulmonary tuberculosis at Hopspital Treatment in the Jayapura City Hospital.